2020
DOI: 10.1111/resp.13869
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training as part of lung cancer therapy

Abstract: Exercise training is playing an increasing role in lung cancer care. Lung cancer is associated with significant burden to the individual and healthcare system. There is now substantial evidence that exercise training is safe, feasible and effective at improving several outcomes in people with lung cancer, especially in those with NSCLC. Exercise is beneficial across the lung cancer disease and treatment pathway, including in patients with early stage disease before and after surgery, and in patients with advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 61 publications
0
43
0
2
Order By: Relevance
“…Physical performance and mobility are closely related to physical activity, 35,36 and physical activity has been suggested to counteract some specific hallmarks of cancer and to prevent chemotherapy‐related adverse events 37 . In addition, the anti‐tumorigenic effect of exercise is related to immunomodulation, particularly by increasing pro‐inflammatory cytokine levels and natural killer cell infiltration in the tumour micro‐environment 38 . Patients with low physical performance may not benefit from these effects, and therefore, these associations may be related to the high incidence of post‐operative adverse events in patients with ‘sarcopenia with limited mobility’.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical performance and mobility are closely related to physical activity, 35,36 and physical activity has been suggested to counteract some specific hallmarks of cancer and to prevent chemotherapy‐related adverse events 37 . In addition, the anti‐tumorigenic effect of exercise is related to immunomodulation, particularly by increasing pro‐inflammatory cytokine levels and natural killer cell infiltration in the tumour micro‐environment 38 . Patients with low physical performance may not benefit from these effects, and therefore, these associations may be related to the high incidence of post‐operative adverse events in patients with ‘sarcopenia with limited mobility’.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to accurately assess preoperative sarcopenia and physical performance because both can be targeted for treatment before and after surgery with various interventions, including nutritional recommendations and rehabilitation 43–45 . Exercise is a non‐pharmacological intervention that improves fatigue, quality of life, pulmonary function, muscle mass, physical performance, and psychological status of patients with lung cancer 37,38 . In addition, the performance of resistance training and use of nutritional supplements, including branched‐chain amino acids, vitamin D, whey protein, and hydroxymethylbutyrate‐enriched milk, play important roles in the prevention and improvement of sarcopenia, 15 and these interventions may result in improved post‐operative outcomes for frail NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since then the number of studies in this field rose substantially and exercise started to be considered a tool for the treatment for cancer-related fatigue [ 146 ], for functional, psychological and emotional well-being [ 147 ] and for cancer cachexia [ 148 ]. Recently, it has been suggested that exercise is a worthy therapy in many cancer treatments at all stages [ 149 ], along with radiotherapy, chemotherapies and immunotherapies [ 150 ], including for cancer-related cognitive impairment [ 151 ].…”
Section: Therapeutic Effects Of Exercise In Cancermentioning
confidence: 99%
“…In recent years, the implementation of pulmonary rehabilitation in patients with lung cancer has gained recognition in the world of medicine. It has been shown that rehabilitation is safe and acceptable to patients; improves fitness, physical efficiency, and oxygen consumption; and reduces fatigue [14,15,[17][18][19]. The reason for this is that exercise training challenges the entire oxygen transport pathway from the lungs, to the circulation, to the tissues-delivering oxygen to the cells.…”
Section: Introductionmentioning
confidence: 99%